Simulating the Second Moment of NMR Spectral line in Ammonium Chloride Single (Global Journal of Science Frontier Research, 2017)
Innovative technique of simulating the second moment of NMR spectral line broadened owing to the magnetic dipole-dipole interaction in crystals with internal molecular motion is suggested. The local hindered molecular motion (HMM) is approximated by the extended angular jump model. The resulting expression of the second moment allows one to evaluate the crystal structure distortion and the dynamical parameters of HMM. The presented theory agrees with the experimental anisotropic second moment of proton NMR spectral line in whole temperature region of the ammonium chloride single crystal investigation.
Keywords: crystallographic point symmetry; hindered molecular motion; nuclear magnetic resonance; second moment; single crystal; symmetry distortion